Visual perception AHOV 2213 lab book - Ahmad, Norsham; Abdul Rahim, Muhammad Afzam Shah (2021)
The first version of the visual perception lab book was created in 2014 and I did some amendments every year to ensure the LOs of the course is achieved. The final version was amended in 2020. This lab book is a compilation of the lab manual and questions used in the Visual Perception course. Visual Perseption is a core course for Optometry programme offered in year 2, semester 1.